Determination of shoulder global range of motion - Tio, Yeni (2015)
The purpose of this study is to quantify the shoulder global range of motion during the activities of daily living for clinical purposes. Existing measuring equipment are complicated, expensive and not applicable for clinical practice. Current method with the manual goniometers has low inter-individual reliability and reproducibility hence a novel global arc of motion shoulder jig was designed specifically for such measurements in this study. Fifteen male participants (23 ± 1.51 years old), with no shoulder pathologies and history of shoulder injuries, participated in this study. They performed a total of eight movements with the optical marker-based motion capture system and on the novel global arc of motion shoulder jig, with at least three repetitions per task. For standardisation purposes, the marker positions on the anatomical landmarks, the definitions of the joint coordinate systems and the rotation sequence of the thorax with respect to the humerus coordinate system recommended by the International Society of Biomechanics were adopted. Euler angles were used to analyse the experimental variables: the angle of elevation and the angle of plane of elevation for each movement. The data collected from the novel global arc of motion shoulder jig were then compared with that of the optical marker-based motion capture system by the Student’s t-test to validate the shoulder jig’s effectiveness. On average, the angles of elevation obtained on the shoulder jig were larger for most movements. At a 95% confidence interval, three out of the four studied activities of daily living were statistically significant. The implication of the results was that, the current shoulder jig is still incapable of obtaining accurate results and should be redesigned to incorporate a larger range of motion of the shoulder. The significance of this study is the ability to quantify the global range of motion of the shoulder joint obtained experimentally via the use of a simple two-dimensional map. The use of the two-dimensional map could be used to compare a patient’s range of motion with a universal mean range of motion of the normal population. This could be used as a tool to evaluate the patient’s progress during treatment.